Kegiatan Marketing PR Rawtype Riot - denis hafidz satriani (UNISBA Press, 2023)
Abstract. PR Marketing is an activity that is commonly carried out in the promotion process for the success of a sale, where through activities designed by the company such as Collaborative activities with stakeholders, limited Edition and the use of social media Instagram with the purpose of introducing products to communicate interesting persuasive information related to the product being sold. on offer. Therefore, this research discusses Rawtype Riot's PR marketing activities, and how Rawtype Riot encourages communication with customers through Instagram social media, as well as collaborating with stakeholders as a way of carrying out marketing activities. The matters discussed in this study are reviewed and based on the PR Marketing theory. This study uses a case study approach with qualitative methods, and uses data processing techniques through interviews, observation, and documentation. Based on the results of research formulated on the findings of Riot Rawtype Marketing Activities are Consistent, Attractive and good promotion in maintaining the exclusivity of Riot Rawtype Products. 1) Rawtype Riot is always interesting in finding relationships in collaboration 2) Consistent in using Limited Edition strategies in marketing its products 3) Promotion Interesting content on Instagram is a differentiator from other competitors. Abstrak. Marketing PR adalah kegiatan yang lazim dilakukan dalam proses promosi demi keberhasilan sebuah penjualan, dimana melalui kegiatan-kegiatan yang di rancang perusahaan seperti kegiatan-kegiatan kolaborasi dengan stakeholder, Limited Edition dan penggunaan media sosial Instagram dengan tujuan mengenalkan produk, mengkomunikasikan informasi persuasif menarik terkait produk yang di tawarkan. Maka dari itu penelitian ini membahas tentang kegiatan marketing PR Rawtype Riot, serta bagaimana Rawtype Riot mendorong komunikasi dengan pelanggan melalui media sosial Instagram, juga Berkolaborasi dengan stakeholder sebagai salah satu cara melakukan kegiatan marketing. Hal-hal yang dibahas dalam penelitian ini ditinjau dan dilandasi menggunakan teori marketing PR. Penelitian ini menggunakan pendekatan studi kasus dengan metode kualitatif, serta menggunakan teknik pengolahan data melalui wawancara, observasi, dan dokumentasi. Berdasarkan hasil penelitian yang di rumuskan pada hasil temuan Kegiatan Marketing Rawtype Riot adalah Konsisten, Menarik dan promosi yang baik dalam mempertahankan ekslusifitasan dari Produk Rawtype Riot. 1) Rawtype Riot selalu menarik dalam mencari relasi dalam berkolaborasi 2)Konsisten dalam menggunakan strategi Limited Edition dalam memasarkan produknya 3)Promosi Konten yang menarik di Instagram menjadi pembeda dari kompetitor lainnya.